Modified oil sorbent from beet pulp for surface water purification from oil - Anna S. Melnikova; Natalia V. Kostryukova (Izvestiâ Tomskogo politehničeskogo universiteta. Inžiniring georesursov, 2025)
Relevance. The sixth and twelfth Sustainable Development Goals are ensuring the rational use of water resources and promoting responsible consumption, production, respectively. Due to the active development of industry, many water resources are subject to anthropogenic pollution, especially as a result of oil spill. The problem of the negative impact of oil and petroleum product spills on the environment poses a threat to public health and ecosystem sustainability, and its solution is an urgent topic not only for Russia, but also for the world as a whole. In this regard, there is a growing demand for an environmentally friendly and efficient low-cost oil sorbent to eliminate the consequences of spills. An innovative area that occupies a special niche is the development of technologies for the creation and use of sorption materials made from plant waste from the agro-industrial complex. Aim. Analysis of the effectiveness of beet pulp modification using microwave radiation and comparison of the parameters of the obtained material with commercial analogues of oil sorbents. Methods. A method for determining the oil capacity and residual concentration of petroleum products in water using the Concentrator KN-2m equipment. Results and conclusions. The authors have determined the optimal parameters of the material modification, such as the size of the granules of the raw material and the processing time. The values of the oil capacity of the obtained sorbent and commercial analogues were determined in laboratory conditions. According to the results of experiments, the sorbent of Profsorb-Ultra has the highest oil capacity. The oil sorbent from modified beet pulp has an oil capacity of 4.3 g/g, which is slightly higher than that of the sorbent from Spill-Sorb. The authors determined oil residual concentration in water after the use of sorbents. The highest oil concentration after purification was when using Profsorb-ultra and Profsorb Eco sorbents, which indicates a low purification efficiency. The efficiency of water purification from oil when using oilcake from beet pulp reached 84.55%, which indicates the high efficiency of the material.